تدريس القراءات القرآنية في بروناي دار السلام الواقع وآفاق التطوير - جمعة أحمد همد آدم (AR-RĀ’IQ, 2022)
It is evidently known that God - glory be to Him - has made it easy to memorise His Book. So He sent it down in many types of readings, to ease the recitation of the Quran for the Ummah and to remove embarrassment and hardship. Muslims have exerted great efforts on Quranic readings in learning and teaching, authoring and publishing, throughout the ages. In this era and with the spread of higher education and the emergence of modern technology - which contributed to the dissemination of legal sciences in general and Quranic readings science in particular - the Islamic world organised a scientific awakening in the renaissance of the Quranic readings, and developed various means of teaching and receiving, and offered specialised programmes in readings’ teaching; which gave a quantum leap to the flourishing of the science of Quranic readings, and to re-establish the Quranic readings from the well-known traditional method, which relied on approval from sheikhs and reading circles (halaqah), by teaching them in institutes and universities using modern technology in spreading them, and the Sultanate of Brunei Darussalam is not an exception to this for the nation is concerned with teaching Quranic readings, spreading the message of memorising Al-Quran, studying its sciences, and fulfilling the Islamic duty in preserving the revelation and its heritage. This topic was set out to find out the reality of teaching Quranic readings in Brunei Darussalam, and to shed light on the efforts made in this field through the programmes concerned with teaching Quranic readings in this country, and to introduce their curricula and teaching methods as to examine the possibility of developing these programmes to keep pace with their counterparts in the world so that student would not be harmed academically when furthering studies abroad.